Compliance of Nurses in Carrying Out Initial Assessment of Hospital Inpathement - Wirananda, Abdi; Kristina, Tri Nur; Dwiantoro, Luky (Indonesian Journal of Global Health Research, 2024)
Initial assessment of hospital inpatients is an important component of patient care, ensuring appropriate treatment planning and improving patient outcomes. Nurses' adherence to initial assessment protocols is critical to maintaining the quality and safety of patient care. This study aims to evaluate nurses' compliance in implementing initial assessment of hospital inpatients and to identify factors that influence nurses' compliance with established protocols. Methodology: This research adopts an approach scoping review with the framework developed by Arksey and O'Malley. Research includes searching articles through databases Google Scholar and Scopus with the keyword "Obedience" "Assasment"AND "Nurse". The research uses the PRISMA method with data sources from Google Scholar and Scopus resulting in a total of 92 articles. The articles were then filtered based on the inclusion criteria, namely using English and Indonesian with a range of 2014-2024 nurses' compliance in implementing initial assessments of hospital inpatients which resulted in 7 articles that met the requirements. Research shows nurses' compliance with initial assessment protocols is influenced by several factors, including training, workload, and organizational support. Addressing these factors through targeted interventions may improve adherence rates and, consequently, patient outcomes. Further research is needed to develop and implement effective strategies to improve nurse compliance in various health care settings.